A one year cross sectional study on role of Wagner’s classification in predicting the outcome in diabetic foot ulcer patients - L., Praveena D.; Uppin, Shashi M.; Shimikore, S. S. (International Surgery Journal, 2018)
Background: Diabetes mellitus-related foot ulceration is very common. Several classification systems for diabetic foot ulcers have been proposed. The present study was intended to assess the role of Wagner wound classification in predicting the outcome of diabetic foot ulcer and also know the grade of Wagner’s classification to which majority of diabetic foot ulcer patients. Methods: This present one year cross sectional study was carried out at the Department of General Surgery. A total of 100 patients with diabetic foot ulcer who presented during the study period were included. The diabetic foot ulcers were graded according to the Wagner’s classification. The relative risk of amputation in different grades of diabetic foot ulcer based on Wagner classification was determined. Results: In this study majority of the patients were males (79%) and the male to female ratio was 3.76:1. The mean age was noted as 55.8±10.45 years. Majority of the patients had duration of ulcer less than one month (88%). Surrounding skin was inflamed in 60% of the patients, necrosis was present in 40% and slough was noted in 98% while 44% of the patients had necrotic tissue. Based on Wagner’s Classification, most of the patients (48%) had Grade II diabetic foot ulcers. With regard to management, in 44% of the patients’ debridement was done and 36% of the patients had disarticulation or amputation in 36%. Of the 48 patients with grade II ulcer, 79% of the patients had healing without amputation. Of the 58 patients with grade I and II diabetic foot ulcers, 82.76% had healing without amputation compared to 17.24% of the patients who needed amputation. Patients with Grade III, IV and V had 3.59 times higher risk of amputation compared to patients with grade I and II. (p<0.001; 95% CI- 1.95 to 6.62). Conclusions: Grading of diabetic foot ulcer based on Wagner’s classification affects and predicts the outcome and the risk of amputation increases with increasing grade. Most of the patients admitted for diabetic foot ulcers in our hospital belonged to Wagner’s grade II (48%).